2020
DOI: 10.3390/biom10050731
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Pharmacological Properties and Phytochemical Profile of Bruguiera gymnorhiza (L.) Lam Using In Vitro Studies, In Silico Docking, and Multivariate Analysis

Abstract: Bruguiera gymnorhiza (L.) Lam. is claimed to effectively manage a number of ailments including diabetes and associated complications. Nonetheless, no attempt has been made to delineate its pharmacological propensities and phytochemical profile. This study was designed to appraise the antioxidant and enzymatic inhibitory properties relevant to the management of diabetes mellitus, obesity, and neurodegenerative and skin disorders. A combination of colorimetric assays and ultra-high-performance liquid chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
2
12
1
1
Order By: Relevance
“…Overall, findings showed that there is a good correlation between the different assays except with metal chelating assay. Such kind of correlation was also observed in several other studies [ 32 , 33 , 34 , 35 ]. The methanol bark extract exhibited the highest antioxidant property with all assays except metal chelating.…”
Section: Resultssupporting
confidence: 86%
“…Overall, findings showed that there is a good correlation between the different assays except with metal chelating assay. Such kind of correlation was also observed in several other studies [ 32 , 33 , 34 , 35 ]. The methanol bark extract exhibited the highest antioxidant property with all assays except metal chelating.…”
Section: Resultssupporting
confidence: 86%
“…The ice plant extract showed a FRAP value in the range of that found by Qasim et al [ 32 ] for 100 medicinal halophyte plants. The ferrous ion chelating activity of the extract ( Table 1 ) was much lower than that reported by Sadeer et al [ 33 ] in an extract from the halophyte Bruguiera gymnorhiza (6–60 mg EDTA Eq/g).…”
Section: Resultscontrasting
confidence: 61%
“…However, P. heyniae displayed the highest metal chelation effects (27.79 mg EDTAE/g) considering metal-chelating properties. Previous studies have also reported a weak correlation between metal-chelating assays and DPPH, ABTS, CUPRAC, and FRAP methods [ 61 , 62 , 63 , 64 ]. An explanation of this discrepancy is related to the different chemical reactions involved in the assays.…”
Section: Resultsmentioning
confidence: 99%